Clinicopathological characteristics of patients with vaginal cancer in the period 1995 to 2017: Klinično patološke značilnosti pacientk z rakom nožnice v obdobju med 1995 in 2017 - Gavrić Lovrec, Vida; Krajnc, Barbara; Kozar, Nejc; Jakob, Nina; Hozjan, Tadeja; takač, Iztok (Acta Medico-Biotechnica, 2021)
Purpose: Vaginal cancer is a rare malignancy that is approximately 3% of all malignant neoplasms of the female genital tract and accounting for approximately 20 new diagnoses each year in Slovenia. The aim of this study was to evaluate characteristics of patients with vaginal cancer and to analyse the epidemiologyand describe clinical features, types of treatments applied and factors affecting occurrence of the disease.Methods: A retrospective study of all vaginal cancers in patients residing in northeastern Slovenia during the years 1995 and 2017 was performed. Patient demographics, disease characteristics, clinical features, referring cytology and histological findings and type of therapy were recorded. Associations among various demographic factors, tumour characteristics, treatments and risk factors of vaginal cancer were evaluated.Results: A total of 33 patients aged 38–87 years were identified over the 23-year period. The mean age of patients was 64 years. Altogether, we found five different types of neoplasia and 97% of affected patients were between 50 and 80 years old. The most common histologic type of vaginal malignancy was squamous cell carcinoma (78%).Conclusion: Our results suggested that in eastern Slovenian population, squamous cell carcinoma is the most common vaginal malignancy; it affected primarily older women. This research is first of its kind in the field of vaginal malignancies in the reported region. Retrieval of data from other medical centres of Slovenia would allow more valuable conclusions.
Keywords: vaginal cancer; epidemiology; clinical characteristics; histology